Scaffolding of Arabic Takhossus program on maharah kalam learning in Qur’anic Junior High School Darul Fattah Bandar Lampung - Hidayat, Surya; Faisol, M.; Muchsin bin Agil, Idrus; Al Faruqi, Mhd Ibnu Hanan (Abjadia : International Journal of Education, 2025)
Sociocultural theory is a theory in sociology and psychology that addresses the importance of culture and society in the development and formation of individuals. One of the main components in the sociocultural theory proposed by Lev Vygotsky is the concept of scaffolding which refers to the form of support or assistance provided by more competent individuals, such as adults, teachers, or even peers, to learners who are trying to understand a concept or complete a particular task The purpose of the research is to observe how the concept of scaffolding in Vygotsky's sociocultural theory in learning maharah kalam in the Arabic takhosus program of Darul Fattah Bandar Lampung Qur'anic Junior High School. Data were collected through observation, interview and documentation. Data analysis techniques are by summarizing data, presenting data and drawing conclusions. The result of this study is that the concept of scaffolding in this program is through two main sources, namely teachers and peers. It is hoped that this research can be a reference for similar research and further research can further develop similar research.